Stability and boundedness of solutions of a kind of third-order delay differential equations (2016)
ABSTRACT: This paper studies the stability and boundedness of solutions of certain nonlinear third-order delay differential equations. Sufficient conditions for the stability and boundedness of solutions for the equations considered are obtained by constructing a Lyapunov functional.